Effect of Annealing Temperatures on the Structural and Optical Properties of ZnO and ZnO:Al Thin Films Prepared By Thermal Evaporation Technique - Makee, Samir A.; Shehab, Alia A.M.; Rehima, Ali M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
We studied the changing of structural and optical properties of pure and Aluminum-doped ZnO thin films prepared by thermal evaporation technique on glass substrates at thickness (800Â±50)nm with changing of annealing temperatures ( 200,250,300 )â„ƒ for one hour. The investigation of (XRD) indicates that the pure and doped ZnO thin films were polycrystalline of a hexagonal wurtzite structure with preferred orientation along (002) plane. The grain size was decreased with doping before annealing, but after annealing the grain size is increasing with the increase of annealing temperature for pure film whereas for the doped films with ratios 1 %, 2 % we found that the grain size is larger than that before annealing. The grain size for doped film with ratio 3 % was decreased with the increase of annealing temperature. The optical measurements showed that the transmittance before annealing is larger for doped films than for pure film and the maximum value is 97.025 % for doped film with ratio 1 %. The transmittance decreased with the increase of annealing temperature. The optical energy gap before annealing increases with the increase of the doping ratio whereas after annealing its value depends on doping ratio .